Utilization of Digital Platform-Based Learning Media: Interest and Learning Achievement in Physical Education at State Elementary School - Aksir, Muh. Ilham; Hasyim; Syafruddin, Muhammad Akbar (ETDC: Indonesian Journal of Research and Educational Review, 2024)
This study's objective is to ascertain how the utilization of digital animation video platforms as a learning medium enhances the engagement and academic achievements of Physical Education students in grade V at Tanggul Patompo I Elementary School, located in Makassar City. This study employs an experimental design, utilizing a pre-test and post-test design. The study's variables include student interest and learning achievement in the context of physical education. In this study, the instrument used was a questionnaire containing statements that would be used to reveal students' interests and learning achievement when implementing physical education. The study provided a digital platform to facilitate the learning process. The sample in this study consisted of one class of 30 students. The results of the study showed that the N-Gain test of interest data had the lowest percentage increase of 75.51%, the highest percentage increase of 94.87%, and the average percentage increase of 84.5%. Meanwhile, the N-Gain test of learning outcome data showed the lowest percentage increase of 55.56%, the highest percentage increase of 8.24%, and an average percentage increase of 68.9%. Therefore, it is concluded that animation video platform-based learning media are quite effective in improving the learning achievement of physical education students in grade V at Tanggul Patompo Elementary School I, Makassar City.